2000
DOI: 10.1046/j.1365-2583.2000.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of the Mediterranean fruit fly, Ceratitis capitata

Abstract: The complete sequence of the mitochondrial genome of Ceratitis capitata has been determined. The circular genome is 15 980 bp long and contains a standard gene complement, i.e. the large and small ribosomal RNA subunits, twenty-two transfer RNA (tRNA) genes and thirteen genes encoding mitochondrial proteins. When comparing the sequence to fragments previously sequenced from other isolates it becomes apparent that interstrain polymorphisms are not rare. These differences are potentially useful for the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 33 publications
7
73
0
1
Order By: Relevance
“…Given its maternal inheritance, small size, lack of recombination and presence of polymorphisms, the mtDNA proved to be a valuable tool to study the various patterns existing in many insect species such as Drosophila (Lewis et al 1995), Phlebotomus (Esseghir et al 1997) and Ceratitis capitata populations (Spanos et al 2000). Initial studies on the medfl y genetic diversity were based on a RFLP-PCR-based approach using the ND5-tRNA-ND4 mitochondrial locus to detect the haplotype variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its maternal inheritance, small size, lack of recombination and presence of polymorphisms, the mtDNA proved to be a valuable tool to study the various patterns existing in many insect species such as Drosophila (Lewis et al 1995), Phlebotomus (Esseghir et al 1997) and Ceratitis capitata populations (Spanos et al 2000). Initial studies on the medfl y genetic diversity were based on a RFLP-PCR-based approach using the ND5-tRNA-ND4 mitochondrial locus to detect the haplotype variants.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the direct analysis of mitochondrial DNA sequences from the ND5 region has uncovered a rich array of distinct haplotypes within populations of the Mediterranean fruit fl y. Th is approach makes it possible to use sophisticated tools for the analysis of networks of intraspecifi c gene genealogies (Posada & Crandall 2001) without sacrifi cing the traditional advantages of using mitochondrial DNA (Steck et al 1996;Spanos et al 2000) to analyze populations of this and other pest species. Furthermore, we have shown that our approach allows for the detailed analysis of highly variable populations, such as those from countries like Tunisia, which had proven to be refractive to analysis using the PCR-RFLP method.…”
Section: Discussionmentioning
confidence: 99%
“…This marker, because of these characteristics, has been widely used in studies of population genetics and evolutionary relationships of many groups of organisms (Avise, 1994;Spanos et al, 2000). ND5 (coding for subunit 5 of NADH dehydrogenase) is one of the most variable genes of mtDNA and has been studied in several species of the Anopheles and Aedes genera (Besansky et al, 1997;Birungi and Munstermann, 2002;MolinaCruz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For the P. sulpitia COI gene, no typical ATN initiator was found in its starting region or in its neighboring trnY sequences. As for the cox1 initiation codon in animals, significantly different cases have been reported, for example, tetranucleotides such as TTAG in Coreana raphaelis (Kim et al, 2006), ATAA in Drosophila yakuba (Clary & Wolstenholme, 1985) are used, while hexanucleotides such as TATTAG in Ostrinia nubilalis and Ostrinia furnicalis (Coates et al, 2005), TTTTAG in Bombyx mori (Yukuhiro et al, 2002), TATCTA in Penaeus monodon (Wilson et al, 2000), ATTTAA in Anopheles gambiae (Beard et al, 1993), Anopheles quadrimaculatus (Mitchell et al, 1993), and Ceratitis capitata (Spanos et al, 2000) are used. Generally, the trinucleotide TTG was assumed to be the cox1 start codon for some invertebrate taxa including insect species, such as Pyrocoelia rufa (Bae et al, 2004), Caligula boisdnvalii (Hong et al, 2008), and Acraea issoria .…”
Section: Protein-coding Genesmentioning
confidence: 99%